Commuting a mundane journey - Gonzales, Erris
The purpose of this thesis is to explore the use of traditional and digital media simultaneously. Growing up, I was fascinated by digital media and techniques. For the work, my objective is to combine together with traditional techniques with reproduction and enhancement capabilities of digital media. As an alternative method in creating stained glass effect, it uses cheap materials such as acrylic sheet, glass paints and sticker paper for printing digital linear images. Using these materials, the work was about an autobiographical narrative of a college student who commutes from provincial home to school and vice versa every week, making it a mundane journey of her commuting experience.